TOWS Analysis of Agricultural Insurance in the Application of a Green Economy (Nusantara Science and Technology Proceedings, 2021)
This research aims to find out whether the APBN (State Revenue and Expenditure Budget) provided by the government is appropriate to support a green economy in the Covid-19 era, especially in the agricultural sector, and wants to know how the role of agricultural insurance is in the welfare of farmers. The method used in this research used a literature review. Sources of data obtained from this research are in the form of books, journals, and internet sites related to the topics discussed. The results show that the implementation of SRI in achieving green economy implementation has been going well, but the State Budget (APBN) provided by the government is not fully suitable to support a green economy. In addition, the role of agricultural insurance in the welfare of farmers is considered a fairly good policy.